A new Civilization and Its Discontents in times of COVID‐19?. (5th May 2021) - Blass, Heribert
Abstract: The Covid‐19 pandemic brings into focus both the burdens on individuals, and the effects on the culture and society in general. In our encounters with our patients, we as psychoanalysts have experienced the broad spectrum of possible reactions to the viral threat, just as it is found throughout society: from real fear to panic or, on the contrary, to a denial of the impending danger. We are facing drastic changes which are connected with painful losses but sometimes also with new possibilities in our accustomed lives. Nevertheless, the loss of trust in the preservation of individual and general health and of economic existence as well goes beyond the individual and leads to tensions and even cracks in the supposed social consensus. Thus, in the relationship of the individual to society, the pandemic exacerbates the ambivalence between self‐interest and solidarity, not infrequently to the point of forming hostile attitudes. In this article, the author explores the question of to what extent it is possible to speak about a "new Civilization and Its Discontents" in light of the increasing social tensions under the conditions of the pandemic. It is the task of psychoanalysis to explicitly name the unconscious conflict between striving for pleasure and happiness or the search for security, in order to also contribute to dealing with the resulting aggression and fear of death in times of pandemic.